Dampak Media Sosial terhadap Pembentukan Opini Publik di Lingkungan Kampus - Eva Diana Sari; Abustan Abustan; Eli Karliani (Jurnal Ilmiah Kanderang Tingang, 2026)
Social media plays a major role in shaping public opinion, including within the campus environment, which serves as a space for academic and social interaction among students. The phenomenon of trial by netizen with the slogan “no viral, no justice” indicates a tendency among students to respond to an issue based on the virality of content on social media rather than through appropriate clarification mechanisms. This study aims to analyze the impact of social media on the formation of public opinion in the campus environment among Informatics Engineering students and to measure the extent to which this phenomenon influences their perceptions and attitudes. The research was conducted using a mixed-methods approach with survey and interview techniques. Data were collected through the distribution of questionnaires to 100 student respondents and in-depth interviews with 10 student informants from the Informatics Engineering Study Program at two higher education institutions in Palangka Raya, namely the University of Palangka Raya (UPR) and STMIK Palangka Raya. The research variables include the intensity of social media use, the level of exposure to viral content, trust in digital information, and the tendency to form opinions based on viral issues. Data were analyzed using descriptive quantitative methods and followed by regression analysis to examine the relationships and effects among the research variables. The results show that the intensity of social media use and the level of exposure to viral content have a significant influence on the formation of students’ public opinion. The majority of respondents (72%) stated that viral issues are considered more important than non-viral ones, and 64% of respondents admitted that they had been influenced by netizen opinions when responding to a campus-related issue. These findings indicate that the phenomenon of trial by netizen has shaped students’ mindsets and behaviors in making judgments about a case, potentially creating digital social pressure on campus institutions. Based on the data obtained, this study concludes that social media has a strong impact on shaping students’ public opinion through the speed of information dissemination, emotionally driven digital interactions, and social pressure arising from the dynamics of virality. Therefore, strengthening digital literacy, media ethics, and guidelines for handling viral issues within the campus environment is necessary to prevent the formation of biased opinions that are not based on facts.